Analisis Efisiensi Usahatani Tumpangsari Jagung dan Kacang Tanah dengan Monokultur Jagung di Desa Kombungo Kabupaten Muna - Wa Ode Fitrianingsih; Wa Embe; Basri Sufa (Agrisurya, 2022)
The purpose of the study was to determine the efficiency of intercropping corn and peanut with corn monoculture in Kombungo Village, Lasalepa District, Muna Regency. Determination of the sample by simple random method using the slovin method at a confidence level of 85% of the population of corn and peanut intercropping with corn monoculture. Furthermore, the two populations were taken by simple random sampling with 19 people each for intercropping corn and peanuts and 19 people for corn monoculture. In this study used cost analysis, revenue analysis and efficiency analysis. The results showed that: (1). The total income of maize and peanut intercropping is Rp. 31,803,885.71 with a total production cost of 1,457,200 so that the farmers' income is Rp. 30,346,685.71/MT/ha, the largest income is contributed by the sale of peanuts. (2). The total revenue from corn farming is 15.337.142.86 with total production costs of Rp. 2.218.952.39 so that the income from farming in the research area is Rp. 13.118.190.48. The R/C value obtained is 8.25. (3). The intercropping corn and peanut farming is more efficient than the corn monoculture farming, which is indicated by the R/C value of the corn and peanut intercropping 17.67 while the corn monoculture has an R/C value of 8.25.